Does specific footwear facilitate energy storage and return at the metatarsophalangeal joint in running? - Willwacher, S.; König, M.; Potthast, W.; Brüggemann, G. P. (Journal of Applied Biomechanics, 2013)
Longitudinal midsole bending stiffness and elasticity are two critical features in the construction of running shoes. Stiff elastic materials (eg, carbon fiber) can be used to alter the midsole bending behavior. The purpose of this study was to investigate the effects of midsole stiffness and elasticity manipulation on metatarsophalangeal (MTP) joint mechanics during running in 19 male subjects at 3.5 m/s. Midsole bending stiffness and elasticity were modified by means of carbon fiber insoles of varying thickness. Stiffening the shoe structures around the MTP joint caused a shift of the point of force application toward the front edge of the shoe-ground interface. Negative work was significantly reduced for the stiffest shoe condition and at the same time a significant increase of positive work at the MTP joint was found. It seems plausible that the increase in positive work originates from the reutilization of elastic energy that was stored inside the passive elastic structures of the shoe and toe flexing muscle tendon units. Further, an increase in midsole longitudinal bending stiffness seems to alter the working conditions and mechanical power generation capacities of the MTP plantar flexing muscle tendon units by changing ground reaction force leverage and MTP angular velocity.